2014
DOI: 10.2528/pierc14033105
|View full text |Cite
|
Sign up to set email alerts
|

Compact Uwb Mimo Antenna With Acs-Fed Structure

Abstract: Abstract-A compact UWB (Ultrawideband) MIMO (Multiple-input multiple-output) antenna with asymmetric coplanar strip (ACS)-fed structure is proposed in this paper. The antenna consists of two modified ACS feeding staircase-shaped radiation elements which are orthogonally placed, and the wideband isolation is achieved through a fence-like stub between them. The effectiveness of the fencelike stub is analyzed. Measured results show that the presented antenna can achieve a broad impedance bandwidth (|S 11 | −10 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Several methods such as polarization diversity, space diversity, slots and stubs in the ground plane, split ground, modified shaped ground plane or combination of these have been proposed to reduce the mutual coupling in wideband MIMO antennas [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Two stair case shaped antennas are placed orthogonally and fed by asymmetric coplanar strip (ACS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods such as polarization diversity, space diversity, slots and stubs in the ground plane, split ground, modified shaped ground plane or combination of these have been proposed to reduce the mutual coupling in wideband MIMO antennas [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Two stair case shaped antennas are placed orthogonally and fed by asymmetric coplanar strip (ACS).…”
Section: Introductionmentioning
confidence: 99%
“…Two stair case shaped antennas are placed orthogonally and fed by asymmetric coplanar strip (ACS). A fence metal stub is used to improve the isolation > 15 dB over 3.1-10.6 GHz [11]. Two inverted L-shaped stubs and a T-shaped slot are introduced in ground plane to lower the mutual coupling < −20 dB over 2.26-6.78 GHz [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported to achieve the wideband and high isolation between the elements of a MIMO UWB antenna [3][4][5][6][7][8][9][10][11]. The neutralized line is a simple decoupling network to improve the isolation and utilized in [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In [9], there is a compact MIMO antenna design with partial ground plane. The MIMO antenna with asymmetric coplanar strip (ACS)-fed structure is proposed in [10]. Good isolation is achieved by inserting fence-like stub and vertical port position.…”
Section: Introductionmentioning
confidence: 99%
“…Various decoupling methods for UWB MIMO antennas to improve performance in multi-path fading channels have been previously reported, for example, double-layer electromagnetic band-gap (EBG) structures for reducing the electromagnetic coupling on a common ground [7], taking the inherent advantage of the self-complementary structure to decouple [8], vertical feeding placement without using any extra decoupling structures [9], introducing reflective units such as parasitic components [10] or protruding ground stubs [11,12], using defected ground structure (DGS) [13] to suppress surface wave, adding neutralization lines (NL) to reduce the coupling current flowing [14]. Overall, most of the previously published decoupling structures are complex and then make them difficult for mass production.…”
Section: Introductionmentioning
confidence: 99%